Penggunaan Uang Kepeng Dalam Tradisi Cacah Jiwa Di Desa Payangan Desa, Kabupaten Gianyar Perspektif Vedanta - Yuliantari, Ni Putu Sarasdewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Uang Kepeng is well known in Balinese society, since the trade between the Chinese and the ethnic Balinese. The high intensity of interaction between ethnic Chinese and Balinese led to a cultural mix between the two ethnicities. One of the effects of such cultural mixing is the use of UangKepeng in Hindu religious rituals. As a cultural object which is the result of a process of cultural mixing, the use of UangKepeng in the traditions and ceremonies of Balinese people is interesting to study. The use of UangKepeng in every ceremony in Bali is also contained in Hindu literature. The value of using UangKepeng can also be seen from the perspective of advaita, visistadvaita and dvaita. This study aims to understand the use of UangKepeng in community life and other factors that contribute to the use of UangKepeng in both tradition and ceremony in Bali. In addition, this study also aims to understand Vedanta's views on the use of UangKepeng in tradition and ceremonies in Bali and people's creativity in preserving and increasing the economic value of UangKepeng. The results of this study indicate that the Hindu community in Bali has a perspective regarding the use of UangKepeng. UangKepeng has a religious meaning because it is closely related to religious ideology. UangKepeng also has economic and mystical significance for the community. The high demand for UangKepeng has led to reproductive and innovative efforts to preserve Uang Kepeng.Â